2020
DOI: 10.1021/acsaem.9b02321
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Evaluation of Kinetics and Interaction Mechanism between Chenodeoxycholic Acid and N719 on Dye-Sensitized Nanofilm Surface

Abstract: The photoanode of a dye-sensitized solar cell is composed of titanium dioxide and a dye adsorbed on the surface. Dye molecules, such as N719 dye, usually agglomerate due to H bond and other factors, forming a multilayer adsorption structure, leading to light loss and electron injection loss. Adding a co-adsorbent to the dye, such as chenodeoxycholic acid (CDCA) molecule, is an effective method to prevent the aggregation of the dye. However, the mechanism of interaction between CDCA and N719 is still unclear. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…[42][43][44] CDCA molecules are almost transparent in visible light region, so the adsorption capacity cannot be obtained by "alkaline solution elution-absorbance" method. [8] Since the fingerprint region of CDCA in infrared absorption overlaps with the fingerprint region of dye molecules, it cannot be distinguished by infrared spectrum. [45] Harms et al [45] successfully studied the effect of co-adsorbent CDCA on D-p-A dye Y123 by QCM and UV-visible absorption spectrum, and found that CDCA reduced the adsorption of Y123, and finally the molecular number ratio of Y123 to CDCA on TiO 2 surface was 1 : 1.7.…”
Section: Quantitative Characterization Of Interfaces Mass In Dsscsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42][43][44] CDCA molecules are almost transparent in visible light region, so the adsorption capacity cannot be obtained by "alkaline solution elution-absorbance" method. [8] Since the fingerprint region of CDCA in infrared absorption overlaps with the fingerprint region of dye molecules, it cannot be distinguished by infrared spectrum. [45] Harms et al [45] successfully studied the effect of co-adsorbent CDCA on D-p-A dye Y123 by QCM and UV-visible absorption spectrum, and found that CDCA reduced the adsorption of Y123, and finally the molecular number ratio of Y123 to CDCA on TiO 2 surface was 1 : 1.7.…”
Section: Quantitative Characterization Of Interfaces Mass In Dsscsmentioning
confidence: 99%
“…Mao et al [37] obtained the adsorption capacity, equilibrium constant, ΔH, ΔS and ΔG of CDCA molecules by changing temperature test (Figure 3 c). Liu et al [8] used QCM combined with UV-visible absorption spectrum to study the mechanism of action of CDCA and N719 in detail (Figure 3 d). N719 adsorption accorded with Langmuir theory, while CDCA adsorption accorded with Freundlich theory.…”
Section: Quantitative Characterization Of Interfaces Mass In Dsscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, CDCA and its derivatives are frequently used as co-adsorbents to enhance the efficiency of DSSCs by inhibiting dye aggregation ( Figure 8 ). In the absence of co-adsorbents the aggregation adversely impacts the performance of DSSC, but, since the co-adsorbent is a competitor to the dye adsorption, a large concentration decreases the dye loading and consequently J sc [ 138 , 139 , 140 ]. So, there is an optimal concentration of co-adsorbent in the solvent bath.…”
Section: Dye Aggregation In Dsscsmentioning
confidence: 99%
“…Co-adsorbents increase the PCEs of the devices improving the open circuit potential and photocurrent density, affecting the distribution and position of localized intraband gap states and suppressing electron recombination in the TiO 2 /electrolyte interface. , The extensively used co-adsorbent is chenodeoxycholic acid (CDCA), a type of bile acid first identified as an efficient additive for DSSCs in 1993 . The effect of CDCA on the performance of DSSCs was deeply studied; CDCA became a benchmark co-adsorbent due to its exceptionally efficient TiO 2 passivation, suppression of back current, ability to prevent dye aggregation, and effect of pushing up the Fermi level of TiO 2 for enhanced charge separation. CDCA is chemically very complex, a rather expensive compound, and dominantly produced by extraction from the animal’s liver . Simpler synthetic compounds were reported as effective co-adsorbents in DSSCs: 4-tertbutyl pyridine, 1-decylphosphonic acid, dineohexyl and diphenyl phosphinic acids, esters of phosphoric and carboxylic acids, and amines, among others .…”
Section: Introductionmentioning
confidence: 99%